Parents' knowledge, attitude, and practice on children's screen time at home and the implications for nurses in promoting health: A cross-sectional study - Arippin, Nur Fatin-Aqilah; Mahmud, Mardiah Haji; Abdul Rahman, Hanif; Aliy-Yuin, Kolinmo-Yumni A.; Swee Ching, Linda Lai; H. Abdul Mumin, Khadizah (Universitas Airlangga, 2023)
Introduction: The present study investigated the parent's knowledge, attitude, practice, and experience of the screen time spent by their children at home aged below 5 years old, identifying the common screen-based devices used, content type, and level of screen time spent by the children. Method: A cross-sectional survey of parents having children aged 0 to 4 years old attending the Maternal and Child Health Care Clinics in four districts in Brunei Darussalam was conducted. A questionnaire was developed through the Qualtrics platform. Data were analyzed using R Studio Desktop version 1.2.1335. The statistical analyses included descriptive statistics and Fisher's exact test. Results: Parents' knowledge, attitude, and practice of screen time spent by their children are generally positive; parents who correctly answered the knowledge section overall average of 30.1% (n=34). Children studied (<2 years old and 3 to 4 years old) were found to spend more time watching television. A statistically significant association was observed between children of both age groups with time spent on tablet device (p=0.037) and (p=<0.001). Also, a significant association between parents' knowledge, attitude and practice with gender of the parents, household income and total number of children was reported. Conclusions: We conclude that the children in our study exceeded the recommended guidelines on screen time behavior and the parents' health knowledge with regard to screen time was poor which emphasized the need for improvement and further study. Keywords: screen time, children, parent's knowledge, parent's attitude, parent's practices